Potential Development of Liquid Smoke from Oil Palm Solid Waste as Biofungicides - Asri Gani; Husni Husni; Akhmad Baihaqi; M. Faisal (Chemical Engineering Diponegoro University, 2014)
This research investigated the potential utilization of solid waste from palm oil industry for liquid smoke production in Aceh Province, Indonesia. The liquid smoke can be applied as bio fungicides in agricultural field. Preliminary experiment on the use of liquid smoke as fungicide at Colletotrichum capsisi fungus which causes anthracnose disease on red pepper was also conducted. The survey on the existing potential/availability of palm oil mill in Aceh shows that there are 30 palm oil mills in eight districts with a total of production capacity 1020 ton/hour. Assuming that 10% of palm oil kernel shells are pyrolized into liquid smoke, Aceh province could produce about 23,868 ton of liquid smoke per year. The preliminary test result towards Colletotrichum capsisi fungus shows that the liquid smoke can be used as fungicides.